Experiences of Nurse Managers regarding evidencebased practice in two public healthcare facilities in the Northern Cape Province - Francis, Jennifer Rose Laureen (Stellenbosch : Stellenbosch University, 2026)
Thesis (MNur)--Stellenbosch University, 2026.